Literature Review The Implementation Of Infection Prevention And Control Programs On The Medical Staff - Gilang Indhira Mustika; Kusbaryanto Kusbaryanto (Universitas Muhammadiyah Yogyakarta, 2021)
Health-related infection (HAI) is a major problem facing hospitals affecting patients as well as healthcare workers around the world. There have not been many published systematic reviews on the implementation of infection prevention and control programs. The aim of this systematic review is to analyze the implementation of infection prevention and control programs in medical personnel. The research phase begins with the formulation of a research question (RQ) and data collection begins with a search for research with qualitative methods at Pubmed, Science Direct, Proquest, GARUDA and Google Scholar on